The influence of Islamic mysticism on Iranian education - Mahmoud Navali (Journal of Philosophical Investigations, 2018)
Mysticism can have many effects on our Iranian cultural and spiritual life. This influence can play a significant role in the future of youth education. In this article, we say that mysticism is a kind of individual or personal approach, but education is a collective and social work. How can one use individual approach in collective work? Our response to this question focuses on describing the concept of freedom and its use in both areas. Freedom in the realm of education is a fundamental issue, while mysticism is a kind of inventive and personal approach and attitude. Freedom in the realm of education is a fundamental problem, while mysticism is a kind of inventive and personal approach and attitude. In this article, at first, we try to describe the characteristics of mysticism that make it possible for a person to gain freedom, and also to mention some problems that may lead to determinism and in such a situation the person will be cornered. This situation makes one ignore his responsibilities to one another.